PENYULUHAN K3 DI RUMAH TANGGA PADA PESERTA SENAM SEHAT KELURAHAN MENTANGOR KECAMATAN KULIM - Hasrianto, Nofri; Redho, Ahmad; Susanti, Nurvi (LPPM Institut Pendidikan Nusantara Global, 2023)
The risk of hazards in the household is quite a lot, such as electrical cables containing potential hazards, if there are parts that are peeled off, then the cable is at risk of causing a short circuit which may result in a fatal fire. In this case, the role of residents is important to know and understand the existence of hazards because they are faced with these hazards every day, as well as gas cylinder/hose leaks, cleanliness of living rooms, kitchens, beds and bathrooms, storage and use of hazardous chemicals or perhaps pet feces, etc. All of these become important to understand about Occupational Safety and Health (OHS). All of these make it important to understand Occupational Safety and Health (OHS) in a domestic setting. There are many examples that we can see from various television news or other media. Most house fires are caused by work accidents either by household assistants or family members who live in the house. Damage to electrical/electronic equipment or leakage of gas cylinders/hoses is also caused by ignorance or neglect of factors that are at risk of causing accidents in the workplace and will ultimately threaten the safety of the residents of the house. Therefore, we provide community service information about household occupational health safety to participants in healthy gymnastics organized every Sunday morning by residents in RT 02 RW 18 Mentangor housing, Kulim, Pekanbaru in the hope that it can increase knowledge in homeowners and households.